2021
DOI: 10.3389/fmars.2021.672210
|View full text |Cite
|
Sign up to set email alerts
|

Observation, Preconditioning and Recurrence of Exceptionally High Salinities in the Adriatic Sea

Abstract: The paper aims to describe the preconditioning and observations of exceptionally high salinity values that were observed in summer and autumn of 2017 in the Adriatic. The observations encompassed CTD measurements carried out along the well-surveyed climatological transect in the Middle Adriatic (the Palagruža Sill, 1961–2020), Argo profiling floats and several glider missions, accompanied with satellite altimetry and operational ocean numerical model (Mediterranean Forecasting System) products. Typically, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 80 publications
7
49
0
Order By: Relevance
“…2g, dropping from about 100 to 650 m (maximum whisker values). The distributions tend to be symmetric in most of the Mediterranean Sea, except for the Adriatic Sea, where a strong LIW bimodality in the depth domain is found, with two peaks located at ∼ 190 and ∼ 500 m (here not shown), in agreement with Kokkini et al (2019) and Mihanović et al (2021). In this respect, Mihanović et al (2021), analysing observed data from CTD measurements, Argo floats, several glider missions, satellite observations, and operational ocean numerical model products, provide a possible explanation for this double-maxima vertical pattern, suggesting that these two peaks may be explained by two concurrent events: the winter convection at the beginning of 2017, which leads higher salinities in the water column, and a very strong inflow of high-salinity waters from the North Ionian Gyre in late winter and spring of 2017, which this time is almost restricted to the surface.…”
Section: Liwsupporting
confidence: 71%
See 3 more Smart Citations
“…2g, dropping from about 100 to 650 m (maximum whisker values). The distributions tend to be symmetric in most of the Mediterranean Sea, except for the Adriatic Sea, where a strong LIW bimodality in the depth domain is found, with two peaks located at ∼ 190 and ∼ 500 m (here not shown), in agreement with Kokkini et al (2019) and Mihanović et al (2021). In this respect, Mihanović et al (2021), analysing observed data from CTD measurements, Argo floats, several glider missions, satellite observations, and operational ocean numerical model products, provide a possible explanation for this double-maxima vertical pattern, suggesting that these two peaks may be explained by two concurrent events: the winter convection at the beginning of 2017, which leads higher salinities in the water column, and a very strong inflow of high-salinity waters from the North Ionian Gyre in late winter and spring of 2017, which this time is almost restricted to the surface.…”
Section: Liwsupporting
confidence: 71%
“…-Abrupt shifts in the LIW depth are found in the Adriatic sub-basin from ∼ 200 to ∼ 500-600 m at different time steps (trend 2.609 ± 115.404 m yr −1 ), highlighting a bimodal behaviour of the LIW depth and an intense dense water production activity, as also shown by Kokkini et al (2019) and Mihanović et al (2021).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This current is northward oriented, whatever the circulation mode of the NIG (cyclonic or anticyclonic; see Figure 2 of Menna et al, 2019b andNotarstefano et al, 2019). The LSW transported by the coastal northward current along the western Greek coast could be responsible for the near-surface salinity maximum observed by Kokkini et al (2018Kokkini et al ( , 2020 in the South Adriatic Pit (SAP) during 2015-2016, by Kassis and Korres (2020) in 2005-2010 and by Mihanovic et al (2021) in 2017. These authors describe an anomalous salinity pattern in the SAP, where, the maximum is located in the near-surface layer (around 100 m depth) instead of in the intermediate layer occupied by the LIW.…”
Section: Discussionmentioning
confidence: 87%